PPE w polskim systemie emerytalnym - Sipa, Magdalena (PPE in Pension System in Poland, 2006)
Pension system in Poland, as majority of pension systems in developed countries, consists of three subsystems referred to as pillars. In the paper the possibilities of saving money for pension benefits in PPE are considered. Moreover, the value of a single payment depending on the insurance seniority and the value of the rate of return is calculated. Furthermore, the cost of the pension premium is compared with the rise of the employee's salary. The article also shows the difference between saving money in PPE and beyond it (e.g. in a bank).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 124-135